Does googling for preconception care result in information consistent with international guidelines: a comparison of information found by Italian women of childbearing age and health professionals - Agricola, Eleonora (BioMed Central, 2013)
BACKGROUND: Preconception counseling is effective in reducing the risk of adverse pregnancy outcomes. The Internet is commonly used by women and health professionals to search for health information. We compared the consistency of preconception information found on the Internet with the recommendations published by American Journal of Obstetrics and Gynecology (AJOG) simulating a web search by women of childbearing age and health professionals. METHODS: We reviewed websites resulting from a Google search performed using search strings selected by Italian women of childbearing age and health professionals. We investigated if retrieved information was consistent with AJOG recommendations for preconception care. Logistic regression was used to compare presence of consistent recommendations between women and health professionals. RESULTS: The highest frequency of correct recommendations was found for folic acid supplementation (39.4% of websites). Consistency of preconception information did not significantly differ between search strategies except for folic acid supplementation. “Communities and blogs” website category provided less frequently correct recommendations compared with “Medical/Public Agency" category (i.e. folic acid supplementation (aOR 0.254; CI 0.098-0.664; p = <0.01). Commercial links, found in 60% of websites, were associated with presence of correct recommendations excepting few items (i.e. physical exercise (aOR 1.127; CI 0.331-3.840; p = 0.848). CONCLUSIONS: Preconception information found is poor and inaccurate regardless of the search is performed by women or health professionals. It is unlikely that information found on the web have any positive impact among women and health professionals in our setting. Strategies to improve preconception information on the web and education of health professionals for web searching of health information should be considered.